WEBTOON-BASED PHYSICS E-MODULE AS ALTERNATIVE MEDIA TO IMPROVE STUDENT'S CRITICAL THINKING ABILITY ON OPTICAL EQUIPMENT MATERIALS - Ayu, Hena Dian; Jaya, Paskalina; Pratiwi, Hestiningtyas Yuli; Jufriadi, Akhmad (Journal of Teaching and Learning Physics, 2022)
This research focuses on developing and analyzing the qualifications, effectiveness, and reactions of e-module users on optical devices to improve critical thinking skills. The advantage of this e-module is that it contains material descriptions, videos, webtoons, and evaluation questions that can be accessed online. The research method uses research and development of the ADDIE model, with five stages: investigating student needs, designing learning media using pixton.com, canva.com, and the Flip PDF Professional application, and developing e-modules that are validated by media expert validators and material, amounting to two people. , product implementation to users, and evaluation of e-modules by teachers and students. Indicators of critical thinking skills tested include interpreting, analyzing, evaluating, and inferring skills. The feasibility of the e-module turned out to be valid by experts in the media and material obtained from the validation questionnaire. The results of the effectiveness of the e-module in improving critical thinking skills showed that the effectiveness was tested on 26 class X SMK students and user responses, namely teachers and students, were very positive.